2020
DOI: 10.26444/aaem/109319
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of scabies in relation to socio-economic and selected climatic factors in north-east Poland

Abstract: Introduction. Scabies is a contagious parasitic disease, a skin infestation caused by Scaroptes scabieri, tiny mites that burrow under the skin. Outbreaks of scabies can be difficult to control and require the implementation of appropriate control programme. Objective. The purpose of the study was to analyze the epidemiology of scabies in northeast Poland, considering socioeconomic and selected climatic factors. Materials and method. The analysis was based on data reports (n=26,362) obtained from the Polish Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…This study showed that the incidence of scabies was higher among children and males, as shown in Table I, due to the closer physical contact among children, particularly within large family units, which facilitates the transmission and explains different rates relative to age and sex indirectly for the spread of scabies. Besides spreading scabies through close direct skin-to-skin contact, infested persons can transmit scabies indirectly by sharing contaminated items with mites such as clothing, bedding, bed linens, furniture, shared hats, and head coverings (Liu et al 2016;Korycińska et al 2020). High rate of scabies recorded in males may be due to their intensive social lifestyle in the community as they work outside their households for long period which increased the chance for exposure to potential mite sources (Otero et al 2004;Hengge et al 2006;Ursani and Baloch 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study showed that the incidence of scabies was higher among children and males, as shown in Table I, due to the closer physical contact among children, particularly within large family units, which facilitates the transmission and explains different rates relative to age and sex indirectly for the spread of scabies. Besides spreading scabies through close direct skin-to-skin contact, infested persons can transmit scabies indirectly by sharing contaminated items with mites such as clothing, bedding, bed linens, furniture, shared hats, and head coverings (Liu et al 2016;Korycińska et al 2020). High rate of scabies recorded in males may be due to their intensive social lifestyle in the community as they work outside their households for long period which increased the chance for exposure to potential mite sources (Otero et al 2004;Hengge et al 2006;Ursani and Baloch 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The essential element in transmitting scabies is the mite's ability to survive and keep infectivity in the external environment. Therefore, a high humidity ratio associated with low-temperature results in a longer survival time of scabies outside the host body (Liu et al 2016;Korycińska et al 2020) Regarding the effect of seasonal variation of weather temperature on head lice, although lice infestation exists throughout all months of the year at different rates, it increases in hot months. There is a significant association between seasonal variation and head lice infestation among IDPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions in cells that do not have adequate ventilation promote the out-of-host survival of scabies and louse [ 7 , 21 , 22 , 23 , 24 ]. Korycińska et al described a positive correlation between air humidity and scabies incidence [ 25 ]. It should be mentioned that, in addition to the procedure of preliminary medical examinations followed by periodic and control check-ups, Polish prisoners have the right to make appointments mainly with the general practitioner [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some past studies had also reported higher prevalence of scabies in children less than 18 years, although with various prevalence figures. 18,19,[23][24][25][26] Higher prevalence of scabies in children is believed to be due to increased exposure to the parasite and lack of immunity of the host. 20 This finding could also be attributed to poorer hygiene practice among children, given the fact that poor personal hygiene is a risk factor for the scabies infestation.…”
Section: Resultsmentioning
confidence: 99%